TECHNOLOGY EDUCATION IN SLOVAKIA AND SCHOOL REFORM - LUKÁČOVÁ, Danka (Journal of Technology and Information Education, 2010)
A State education program, which fundamentally changes the content, methods and forms of all levels of education, was approved in year 2008. The State education program for schools according to the new school law is a hierarchically top project of education, which involves a frame model of an absolvent, frame curriculum of the educational level and its syllabus. The optional educational content is fulfilled in the school education program, which represents the second level of the participation management model. It gives the schools the possibility to specialize and fit the student needs and interests. According to the educational content we are going to focus on the quantity and quality of the technology education on the primary schools, as the praxis requests of the technical knowledge are on the rise. [PUBLICATION ABSTRACT]